(untitled) (Research, Society and Development, 2020)
Objective: To characterize the clinical and sociodemographic profile of patients with malignant tumor wounds treated at a university hospital. Methodology: This is a descriptive study with a quantitative approach carried out at Hospital Universitário Antonio Pedro between 2014 and 2016. A semi-structured form was applied to record clinical and sociodemographic data from medical records for document analysis and during follow-up of medical consultations. nursing, being analyzed by the average of central tendency. Results: The sample consisted of 13 patients, (76.92%) being female and (23.08%) male, aged between 29 and 75 years, with an average of 59 years. Most were in palliative care (53.83%) with a predominance of Karnofsky Performance Status of 40% (23.08%). Breast cancer was present in (53.85%) of the sample, with etiology of infiltrating ductal carcinoma (46.15%). The lesions were predominantly located in the breast (53.85%), of the malignant ulcerative wound type (53.85%) in stage III (46.15%), with development after tumor resection surgery (30.77%) and spontaneously (30.77%). The following symptoms were recorded: pain (92.30%), exudate (84.62%), bleeding (53.85%) and odor (38.46%), with a predominance of the use of the following wound cover products: mineral oil (69.23%) and Metronidazole (23.08%). Conclusion: Breast cancer and female patients have a higher prevalence of malignant tumor wounds and symptoms. Understanding the profile of patients with these injuries supports care actions tailored to the demands of this clientele.